Exchange Rate and Stock Price Nexus: Evidence from Ghana - Peter Arhenful; Richard Fosu; Mathew Owusu-Mensah (Journal of Social and Development Sciences, 2022)
This study aimed at investigating the link between the Ghanaian exchange rate and stock prices from July 2007 to December 2019, to establish whether appreciation in exchange rate causes stock price increases or otherwise. The Ghana Stock Exchange's (GSE) All-Share Index; served as a proxy for stock prices, while nominal monthly exchange rates for the Ghana Cedi in terms of the US Dollar were utilized as a proxy exchange rate. The Pearson's Product Moment Correlation test was employed to evaluate the link between the two variables, and the Augmented Dickey-Fuller (ADF) test was employed to determine the data's stationarity qualities. The series were all non-stationary since they had unit roots; however, stationarity was attained at the first difference. The results of the regression and correlation analysis conducted revealed that the two macroeconomic variables are negatively connected in the Ghanaian context. In view of the negative association between the exchange rate and stock prices in Ghana, the study advises policymakers to be cautious when implementing exchange rate measures.